우리나라 폐경여성의 구강건강관리행태와 치과치료여부와의 관련성 - 한여정 (한국구강보건과학회지, 2023)
Objectives: Using the raw data of the 7th (2016-2018) Korean National Health and Nutrition Examination Survey, this study aimeds to provide basic data for the the prevention and management of oral diseases in postmenopausal women by identifying the relationship between oral health behaviors and dental care. Methods: Data of postmenopausal women were statistically analyzed using frequency analysis, cross analysis, and logistic regression analysis in SPSS Statistics version 26.0. Results: The odds ratio for oral diseases was low in postmenopausal women who attended annual oral examination, used dental floss, interdental brush, and electric toothbrush, and were when toothbrushing was performed 2-3 times or 4 times per day. Conversely, the odds ratio for periodontal disease treatment, root canal treatment, dental extraction or oral cavity surgery, and dental prosthesis fabrication and repair was high. Conclusions: These study findings provide basic data for the development of oral health policy in the prevention and management of oral diseases postmenopausal women KCI Citation Count: 0